THE DECONSTRUCTION OF MAIN CHARACTER IN IN GURU AINI NOVEL BY ANDREA HIRATA: DERRIDA PERSPECTIVE - Nia Kurniawati; Zuriyati Zuriyati; Saifurrohman Saifurrohman (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: Guru Aini is a prequel to Andrea Hirata's Orang Biasa novel. This study aims to describe the forms of thought of the Guru Desi's main character and the reversal of the binary opposition hierarchy using Derrida's deconstruction theory. The data in this study were the texts taken from the novel Guru Aini which outlines the forms of thought and the reversal of the binary opposition hierarchy. Employing qualitative approach, the data source in this research is the novel of Guru Aini. Data collection methods used were reading, recording and interpretation techniques. Guru Desi as the main character in the novel Guru Aini is a bad-tempered, intolerant and apathetic person. After a reversal of the binary opposition hierarchy, Desi actually has a patient character, and she basically also has positive characters such as tolerance, and optimism within herself. Keywords: Deconstruction, binary opposition, novel, Guru Aini.